Reference genome for the Northern bat (Eptesicus nilssonii), a most northern bat species - Laine Veronika N.; Pulliainen Arto T.; Lilley Thomas M. (Oxford University Press, 2025)
The northern bat (Eptesicus nilssonii) is the most northern bat species in the world. Its distribution covers whole Eurasia, and the species is thus well adapted to different habitat types. However, recent population declines have been reported and rapid conservation efforts are needed. Here we present a high-quality de novo genome assembly of a female northern bat from Finland (BLF_Eptnil_asm_v1.0). The assembly was generated using a combination of Pacbio and Omni-C technologies. The primary assembly comprises 726 scaffolds spanning 2.0 Gb, represented by a scaffold N50 of 102 Mb, a contig N50 of 66.2 Mb, and a BUSCO completeness score of 93.73%. Annotation of the assembly identified 20,250 genes. This genome will be an important resource for the conservation and evolutionary genomic studies especially in understanding how rapid environmental changes affect northern species.